Caregiver knowledge of obstructive sleep apnoea in Down syndrome. Issue 1 (22nd November 2022) - Giménez, S.; Tapia, I. E.; Fortea, J.; Levedowski, D.; Osorio, R.; Hendrix, J.; Hillerstrom, H.
Abstract: Background: Down syndrome (DS) population has a very high prevalence of obstructive sleep apnoea (OSA), but this remains underdiagnosed. Hence, we aimed to evaluate caregiver's knowledge of OSA and related sociodemographic factors that could contribute to OSA screening patterns in this population. Methods: An online survey though the LuMind IDSC Foundation focused on OSA diagnosis, treatments and the number of sleep studies performed. Data were compared between subjects born before and after the American Academy of Pediatrics (AAP) recommendations for OSA screening. Results: Of the caregivers, 724 (parents 96.3%), responded to the survey. The median [interquartile (IQR)] age of the subjects with DS was 12 [20;7] years. The majority (84.3%) had sleep apnoea diagnosis, and half of them were initially referred for a sleep study due to disturbed sleep symptoms. Only 58.7% of the responders were aware of the AAP recommendations. This was linked to higher socioeconomic and/or educational level and to an earlier OSA diagnosis. The median (IQR) age of OSA diagnosis was lowered after the AAP guidelines publication compared with before its publication (3 [4;2] years vs. 10 [18;5] years, P < 0.000). Adenotonsillectomy (81.9%) and continuous positive airway pressure (61.5%) were the most commonly prescribed treatments. Few had discussed other new therapies such as hypoglossal nerve stimulation (16.0%). Only 16.0% of the subjects repeated the sleep study to monitor OSA with ageing, and 30.2% had to wait more than 4 years between studies. Conclusions: This study reinforces the need to improve OSA knowledge of caregivers and clinicians of individuals with DS to promote an earlier diagnosis and optimal treatment of OSA in this population.